Digitalization and Its Impact on Health Service Marketing Management: A Literature Review - Alfiery Leda Kio; Ni Luh Ayu Citra Citra Mutiarahati (Indonesian Journal of Global Health Research, 2024)
Digitalization has brought significant changes to various sectors, including the healthcare industry. This research is important because digitalization is changing the marketing strategies of healthcare services. Understanding its impact helps healthcare institutions improve services, efficiency, and patient reach effectively in the digital era. This research is a literature study using a systematic literature review (SLR) approach. The articles in this research were obtained from Google Scholar, ScienceDirect, PubMed, and Emerald Insight through keyword searches related to the digitalization of healthcare service marketing during the period 2020–2025. From the search results, 6 relevant and high-quality articles were selected for analysis. The review was conducted systematically by thoroughly reading the articles to identify the main themes and the impact of digitalization on the management of healthcare service marketing. Based on the analysis of existing literature, the results of the study indicate that the application of big data, artificial intelligence (AI), telemedicine, and digital platforms have changed the way healthcare providers design and execute marketing strategies. Big data enables more personalized and data-driven marketing, while AI increases efficiency through predictive analytics that personalize the patient experience. Telemedicine has expanded the reach of healthcare services to remote areas, while digital platforms improve two-way interactions with patients. However, challenges that still exist include data security issues, patient privacy, and access to technology in some areas. This study concludes that despite the challenges, the application of digitalization in healthcare marketing provides great opportunities to improve service quality, efficiency, and patient engagement, as well as strengthen the competitiveness of healthcare providers.